Frames and operator theory in analysis and signal processing - Larson, David R; Larson, David R; Massopust, Peter; Nashed, Zuhair; Nguyen, Minh Chuong; Papadakis, Manos (Providence, American Mathematical Society, 2008)
This volume contains articles based on talks presented at the Special Session Frames and Operator Theory in Analysis and Signal Processing, held in San Antonio, Texas, in January of 2006.